Contribution of Chymase-Dependent Angiotensin II Formation to the Progression of Tubulointerstitial Fibrosis in Obstructed Kidneys in Hamsters - Yu-Yan Fan; Akira Nishiyama; Yoshihide Fujisawa; Hiroyuki Kobori; Daisuke Nakano; Junji Matsuura; Naoki Hase; Hirofumi Hitomi; Hideyasu Kiyomoto; Hidenori Urata; Masakazu Kohno (Elsevier, 2009)
Recent studies indicate a role of chymase in the regulation of angiotensin II (AngII) formation in cardiovascular and renal tissues. We investigated a possible contribution of chymase to AngII formation and to renal fibrosis in unilateral ureteral obstruction (UUO). Eight-week-old Syrian hamsters were subjected to UUO and treated with vehicle, the specific chymase inhibitor (CI) 4-[1-(4-methyl-benzo[b]thiophen-3-ylmethyl)-1H-benzimidazol-2-ylsulfanyl]-butyric acid (50 mg/kg, twice a day, p.o.), or the selective AT1-receptor blocker olmesartan (10 mg/kg per day, p.o.) for 14 days. UUO-induced renal interstitial fibrosis was associated with increases in renal mRNA levels of α-smooth muscle actin (SMA), type I collagen, and transforming growth factor (TGF)-β. The UUO hamsters showed markedly higher AngII contents and increased AT1-receptor mRNA level in the obstructed kidney than sham-operated ones. In contrast, angiotensin-converting enzyme (ACE) protein expression was significantly lower in UUO hamsters. In UUO hamsters, treatment with CI or olmesartan significantly decreased AngII levels in renal tissue and mRNA levels of α-SMA, type I collagen, and TGF-β and ameliorated tubulointerstitial injury. On the other hand, neither CI nor olmesartan changed systolic blood pressure, renal ACE, and AT1-receptor protein levels. These data suggest that chymase-dependent intrarenal AngII formation contributes to the pathogenesis of interstitial fibrosis in obstructed kidneys of hamsters. Keywords:: chymase, angiotensin II, angiotensin-converting enzyme, unilateral ureteral obstruction